Methane adsorption capacity of shale samples from Western Australia - Zou, Jie; Rezaee, Reza (TAYLOR & FRANCIS LTD, 2020)
To examine the influence of clay minerals on methane adsorption in shales, shale samples with low total organic carbon (TOC), ranging from 0.23 to 3.2 wt%, were collected from the Canning and Perth basins, Western Australia. The collected shale samples were measured on gas adsorption experiments: high-pressure methane adsorption and low-pressure nitrogen and carbon dioxide adsorption. Geological controlling factors of methane adsorption capacity for the studied samples were analysed based on a classification of TOC: low-TOC (<1.5 wt%) and high-TOC (>1.5 wt%) samples. The results show that the contribution of organic matter to the methane adsorption capacity of the studied samples is limited. The clay content appears to have a good relationship with the methane adsorption capacity, especially for the low-TOC (<1.5 wt%) samples, which is also supported by the Brunauer–Emmett–Teller surface area. TOC-normalised methane adsorption capacity decreases with increasing thermal maturity for the high-TOC (>1.5 wt%) samples. Furthermore, adsorption affinity of methane, described by the reciprocal of Langmuir pressure, is positively related to the micropore volume and Tmax for the high-TOC samples (>1.5 wt%). (1) A weak relationship exists between TOC and methane adsorption capacity and clay minerals dominate methane adsorption capacity for low TOC (<1.5 wt%) shale samples. (2) Methane adsorption capacity per wt% TOC decreases with increasing thermal maturity for high TOC samples and may result from changes in surface chemistry or roughness of pores. (3) Affinity of adsorption for the high TOC samples is positively related to the micropore volume and thermal maturity.